Perancangan Sistem Informasi Penjualan Dan Persediaan Barang Berbasis Web Pada Toko Wonder Paint - Sutoyo, Mochammad Arief Hermawan; Patricia, Agnes; Qusyairi, Ahmad Rabbani; Carenina, Babel Tio; Khairullah, M.Afif Dzaki; Wijaya, M. Rizky; Andiko, Virginia Casanova (Universitas Muhammadiyah Metro, 2022)
Data management at the WonderPaint paint shop still uses a system that is not yet computerized, which is still recording in the ledger according to its needs at each sale and of course it takes quite a long time to process the data. For inventory, store owners record inventory manually so that it will be difficult to check which items should be purchased to meet inventory or if there is product loss. In addition, in making documents or sales transaction reports only in the form of sheets of paper, the integrity and security of the document is not guaranteed in the event of a complaint. So the author try to research a website's information system that is expected to be able to help administrator or shop owners in recording sales, inventory and help maintain the security of these documents where the admin will be easier to input, and the data will be neater and more efficient. The research method used is waterfall method for the system design. In conclusion, the program is well executed for the store and authors hoped that this system will be very helpful for the store to simplify and speed up their work in processing data